Case Study: Improved Round Robin Algorithm - Putra, Tri Dharma; Purnomo, Rakhmat (Sinkron : jurnal dan penelitian teknik informatika, 2022)
In this journal, discussion is given to analyse the improved round robin algorithm more thoroughly. Round robin algorithm plays a significant role to be used in embedded systems. Round robin algorithm usually applied in real-time systems. Here, three case studies are given, and also the analysis of each case study. Comparisons are given about the average turn around time and average waiting time, also number of context switching between the three case studies. Improved round robin algorithm, is a modification from the generic round robin algorithm. In improved round robin algorithm if the remaining burst time is less than the time slice that is allocated, then the currently running process is continue to be executed. Then finish the currently running process from ready queue and execute the next ready queue. Three case studies are given with three different time quantum, which are 3, 4, and 5 ms. The result of this case study analysis is that, the efficiency of the quantum 5 ms is the most effective one. There is an increase of 50% context switching from quantum 3 to quantum 5. And for average turn around time we get 13.13% reduction in efficiency. While in average waiting time we get reduction 12.08% efficiency.